FINDING THE FIRST EMPEROR OF THE LAST BYZANTINE DYNASTY: MICHAEL VIII PALAIOLOGOS’ LEAD SEAL FROM KOCHANI (Годишен зборник на Филозофски факултет - Скопје, 2022)
The lead seal of Michael VIII Palaiologos found among several medieval artifacts during the excavation of the site Gorno Gradishte, v. Dolno Gratche, Kochani, its bearer and its location were an occasion for re-immersion in the turbulent waters of the 13th century and an attempt to shed additional light on its numerous and in places, dark layers. This paper tries to give a wider archaeological context to the seal and at the same time, to insert that archaeological context in the historical reading of the man whose name will remain engraved in the annals of history as the one who managed to resurrect Byzantium and his connection with this area.